8.5 µm‐Thick Flexible‐Rigid Hybrid Solid–Electrolyte/Lithium Integration for Air‐Stable and Interface‐Compatible All‐Solid‐State Lithium Metal Batteries (Adv. Energy Mater. 24/2022). Issue 24 (23rd June 2022) - Zhang, Kun; Wu, Feng; Wang, Xinran; Weng, Suting; Yang, Xiaoyu; Zhao, Huichun; Guo, Ruiqi; Sun, Yuheng; Zhao, Wenbin; Song, Tinglu; Wang, Xuefeng; Bai, Ying; et al.
Abstract : Li Metal Anodes In article number 2200368, Xinran Wang, Ying Bai, Chuan Wu and co‐workers develop air‐stable and interface‐compatible PEGMA‐Li1.5 Al0.5 Ge1.5 (PO4 )3 ‐lithium integration, taking advantage of a record‐breaking thin layer, sufficiently high ionic conductivity, and flexible‐rigid mechanical properties that synergistically solve problems encountered by all solid‐state lithium metal batteries (ASSLMBs). This first‐of‐its‐kind integrated structure provides a new paradigm to assemble ASSLMBs in ambient condition, paving the way toward ASSLMBs with high safety and high energy density.